Peran Brand Awareness, Brand Image, dan Brand Trust dalam Membangun Brand Loyalty Pengguna Smartphone Samsung di Kabupaten Nias Barat - Riang Santi Darni Zai; Yugi Setyarko (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to determine the role of brand awareness, brand image, and brand trust in building brand loyalty among users of Samsung smartphones. The data source used in this study is primary data collected through questionnaires. The research population consists of consumers who use Samsung smartphones in West Nias Regency. A survey method was employed, with a sample size of 100 respondents who are Samsung users. The sampling technique applied was non-probability sampling, specifically using purposive sampling, and the sample size was determined using the Lameshow formula, with 100 respondents selected. The data analysis was conducted using SPSS version 22 software. The results of this study indicate that brand awareness, brand image, and brand trust all have a positive and significant impact on brand loyalty. Among these factors, brand trust emerged as the most influential element in fostering brand loyalty. This highlights the importance of trust in maintaining long-term customer relationships and ensuring that consumers remain committed to the Samsung brand. Brand trust can be built through consistent product quality, transparent communication, and delivering on promises made to customers. Additionally, brand awareness and brand image are also critical in influencing consumer perception and encouraging repurchase behavior. High brand awareness ensures that consumers recognize the brand, while a strong brand image fosters positive associations with the brand. Companies should focus on enhancing these three aspects in order to build stronger customer loyalty. The results of this study can serve as valuable insights for businesses, particularly in the smartphone industry, to improve their customer retention strategies by strengthening brand loyalty through effective brand management practices.